Too hard to decarbonize: insights from a decision support tool for the Greek maritime operations - Koundouri, Phoebe; Alamanos, Angelos; Deranian, Christopher; Andres Garcia, Jorge; Nisiforou, Olympia A. (My University, 2025)
The Greek maritime sector, one of the largest in the world, faces multiple economic, environmental and development challenges, requiring careful long-term investment decisions. In this paper we present the application of a free, open-source investment decision support tool we have developed, the MaritimeGCH, applied for the Greek fleet. We quantify the effect of two main interventions for a cost-effective carbon abatement, under the recent EU environmental regulations: the implementation of mature on-ship emission reduction technologies and transition scenarios to cleaner fuels. While significant emissions are achievable, even ambitious interventions fall short of fully decarbonizing the sector by 2050. This suggests that a more unified set of policy solutions are needed to achieve the national commitments.
Keywords: decarbonization; energy efficiency; fuels; shipping